Pneumococcal and influenza vaccination coverage of heart failure patients: still a long way to go. (14th October 2021) - Maire, A; Chapet, N; Laugier, M.L; Laffont-Lozes, P; Rigoni, M; Audurier, Y; Aguilhon, S; Leclercq, F; Pasquie, J.L; Breuker, C; Jalabert, A; De Barry, G; et al.
Abstract: : In patients with heart failure (HF), respiratory infections are responsible for acute exacerbation and increased hospitalization. Vaccination may reduce the incidence and/or severity of respiratory infections, and thereby, reduce the risk of HF exacerbation. Despite current recommendation, vaccination coverage (VC) for patients with HF remains far too limited. To study the VC of HF patients followed in our hospital and to precise the strategies desired by the patients in order to carry out the vaccination. This was a prospective monocentric descriptive study conducted between December 2019 and January 2021. Patients with HF history hospitalized in cardiology unit (CU) and patients in a HF telemonitoring program (TP) were included. An interview was conducted by a pharmacist to find out the patient's vaccination status regarding influenza and pneumococcus, together with socio-demographic clinical data. During the interview for non-vaccinated patients, opinion and willingness to be vaccinated were obtained. Data from 335 patients were collected (185 in CU, 150 in TP). The mean age was 69.3 years, and sex ratio was 2.6. About 65% were vaccinated against influenza in the last year (60% in CU, 72% in TP, p=0.022) and 22% had pneumococcal vaccination in the last 5 years (11% in CU, 35% in TP, p<0.001). Respectively 64% of patients with HF with reduced ejection fraction (HFrEF) and 67% of patients with HF with preserved ejection fraction (HFpEF) were vaccinated against influenza (p=0, 63) against 25% of patients with HFrEF and 19% with HFpEF for pneumococcus (p=0, 27). 68% of the patients were in favour of the vaccination, 23% had a mixed opinion and 9% were against it. Among patients not vaccinated against influenza or pneumococcus, 17% refused to be vaccinated. Among unvaccinated patients who consider vaccination, 69% wanted to be vaccinated by their general practitioner (GP) and 7% wanted to be vaccinated by their cardiologist. Almost 1/3 of unvaccinated patients who were included in CU wanted a vaccine prescription at discharge. Among the vaccinated patients, information on the need to be vaccinated had been provided to them mostly by health insurance (73%) and their GP (19%) for the influenza vaccine and by their cardiologist (55%) and GP (32%) for the pneumococcal vaccination. The VC of HF patients remains insufficient, particularly against pneumococcus, as described by Kopp and al. Patients in TP are more vaccinated than patients in CU, which could involve better management. Moreover, the low rate of vaccinated patients is mainly explained by a lack of awareness, as most of the unvaccinated would like to be vaccinated. About 2/3 of patients wanted to be vaccinated by their GP, and thus play a major role in their global care. The higher vaccination rate for influenza, which unlike pneumococcus benefits from a national vaccination campaign, demonstrates that improvements are needed in the institutional promotion of vaccination for HF patients. Funding Acknowledgement: Type of funding sources: None.